Organizational Culture, Organizational Commitment, and Job Satisfaction on Employee Performance Using OCBas an Interveningat State-Owned Enterprises Insurance Company in Batam City - Irfan Ardiyansah; Muhammad Donald Mon (Business and Entrepreneurial Review, 2023)
The application of AKHLAK as the value and culture of SOE companies reflects on each individual employee to always provide the best performance for the company and the country. Since 2020, AKHLAK has become a value and commitment for every individual in the company to achieve more performance in terms of employee obligations and even beyond the standardization of the work provided or what is known as OCB (Organizational Citizenship Behaviour) and employee job satisfaction in terms of employee rights at SOE. The researcher took a sample of SOE Insurance companies in Batam City because Batam is a metropolitan city with an advanced economic aspect, a low minimum wage index, and the highest population in the Riau Archipelago Province. Researchers used quantitative research methods that aimed to examine the influence of organizational culture, organizational commitment, and job satisfaction on employee performance as mediated by OCB in 113 samples distributed through the medium of questionnaires at Insurance Holding SOE companies in Batam City. The results showed that, by direct test, organizational culture, organizational commitment, and job satisfaction influence OCB, as well as the effect of job satisfaction on employee performance. Organizational culture and organizational commitment do not affect employee performance. From the results of the indirect effect test, organizational commitment and job satisfaction affect employee performance with OCB as a mediating variable. With OCB as a moderating variable, organizational culture has no effect on employee performance.